2006
DOI: 10.1099/mic.0.28552-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an iron-regulated gene, chtA, required for the utilization of the xenosiderophores aerobactin, rhizobactin 1021 and schizokinen by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa utilizes several xenosiderophores under conditions of iron limitation, including the citrate hydroxamate siderophore aerobactin. Analysis of the P. aeruginosa genome sequence revealed the presence of two genes, chtA (PA4675) and PA1365, encoding proteins displaying significant similarity to the aerobactin outer-membrane receptor, IutA, of Escherichia coli. The chtA and PA1365 genes were mutated by insertional inactivation and it was demonstrated that ChtA is the outer-membrane receptor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 70 publications
(40 reference statements)
4
54
2
Order By: Relevance
“…Similarly, the ChtA receptor in Pseudomonas aeruginosa is able to recognize and transport citrate-containing hydroxamate-type xenosiderophores such as aerobactin, rhizobactin 1021, and schizokinen. 34) In any event, it should be noted that these receptors for multiple ferric siderophores contain the conserved amino acid residues in the TonB boxes involved in the interaction of these receptors with the TonBExbB-ExbD complex as the energy supplying system. 13,30) In contrast, little is known about multiple receptors specific to an inherent siderophore, with the exception of the type 1 ferric pyoverdine receptors, FpvA and FpvB, in P. aeruginosa 35) and the ferric vibrioferrin receptors, PvuA1 and PvuA2, in Vibrio parahaemolyticus.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the ChtA receptor in Pseudomonas aeruginosa is able to recognize and transport citrate-containing hydroxamate-type xenosiderophores such as aerobactin, rhizobactin 1021, and schizokinen. 34) In any event, it should be noted that these receptors for multiple ferric siderophores contain the conserved amino acid residues in the TonB boxes involved in the interaction of these receptors with the TonBExbB-ExbD complex as the energy supplying system. 13,30) In contrast, little is known about multiple receptors specific to an inherent siderophore, with the exception of the type 1 ferric pyoverdine receptors, FpvA and FpvB, in P. aeruginosa 35) and the ferric vibrioferrin receptors, PvuA1 and PvuA2, in Vibrio parahaemolyticus.…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa strains have w30 genes encoding TonB-dependent receptors (TBDRs), which are involved in the uptake of ferrisiderophores (Cornelis & Bodilis, 2009). Receptors for mycobactin and carboxymycobactin (Llamas et al, 2008), ferrichrome and ferrioxamine (Llamas et al, 2006;Cuív et al, 2007;Hannauer et al, 2010), rhizobactin, aerobactin and schizokinen (Cuív et al, 2006), and vibriobactin (Elias et al, 2011) have all been identified. Given the evidence to date, P. aeruginosa appears to have the greatest capacity for siderophore piracy in the CF lung microbiome.…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…citrate (Cox, 1980b;Harding & Royt, 1990)]. While outer-membrane receptors for most of these heterologous siderophores have been identified (Banin et al, 2005;Cuiv et al, 2006;Ghysels et al, 2005;Llamas et al, 2006Llamas et al, , 2008Poole et al, 1990), additional (e.g. periplasmic or inner-membrane) transport components are generally not evident from the genome sequence.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa produces two siderophores, pyoverdine (Meyer & Hornsperger, 1978;Poole et al, 1991;Visca et al, 2007) and pyochelin Heinrichs et al, 1991;, though the organism is also able to utilize several siderophores produced by fungi and other bacteria (Cornelis et al, 1987;Cuiv et al, 2006Cuiv et al, , 2007Llamas et al, 2006Llamas et al, , 2008Meyer, 1992;Meyer et al, 1999;Poole et al, 1990), as well as additional molecules with Fe-chelating ability [e.g. citrate (Cox, 1980b;Harding & Royt, 1990)].…”
Section: Introductionmentioning
confidence: 99%